Exosome-mediated miRNA delivery: a molecular switch for reshaping neuropathic pain therapy - Ziqing Wei; Ziqing Wei; Chunhui Guo; Chunhui Guo; Hang Zhou; Hang Zhou; Yanling Wu; Yanling Wu; Xudong Zhou; Jibing Chen; Fujun Li; Fujun Li (Frontiers in Molecular Neuroscience, 2025)
Neuropathic pain (NP) is a chronic condition caused by nerve injury or disease. It remains a therapeutic challenge because conventional drugs have limited efficacy and cause adverse effects. Exosomes, with the ability to cross the blood-brain barrier, low immunogenicity, and tissue-homing capacity, have emerged as promising nanovehicles for precise microRNA (miRNA) delivery to modulate key NP pathologies such as neuroinflammation, neuronal hyperexcitability, mechanical allodynia, and thermal hyperalgesia. In this review, we highlight recent advances in exosome-mediated miRNA therapy for NP. We also elucidate the molecular mechanisms and unique advantages of exosomes as both delivery platforms and intrinsic therapeutic agents. We synthesize evidence from preclinical models and initial clinical-stage studies, addressing translational challenges in scalable production and targeted delivery. Through sustained innovation and multidisciplinary collaboration, exosome-based miRNA delivery systems demonstrate transformative potential to overcome current therapeutic limitations, enabling novel NP management strategies.